Brain Natriuretic Propeptide as an Early Marker of Bronchopulmonary Dysplasia or Death in the Preterm Newborn - Montaner, Alicia; Pinillos, Raquel; Galve, Zenaida; Boix, Hector; de la cuesta, Carmen Ruiz; Jimenez, Lorenzo; Samper, Pilar; Rite, Segundo (Klinische Pädiatrie, 2017)
Aim To investigate whether increased brain natriuretic propeptide (NT-proBNP) levels at 48 to 72 h of life are associated with the development of bronchopulmonary dysplasia (BPD) or death in premature neonates.Methods A retrospective study was performed in neonates born before 32 weeks’ gestation or with birth weight below 1500 grams, in whom NT-proBNP determination and echocardiography were performed at 48 to 72 h of life. Associations between NT-proBNP levels and the combined outcome BPD or death were analyzed using multivariate logistic regression analysis.Results 117 neonates with mean gestational age 27.8±2.1 weeks and birth weight 949.7±267.5 grams were included. Forty (34.2%) had an outcome of BPD or death. The risk of this combined outcome was found to be 3.95-fold higher (OR 3.95; 95% CI 1.1–14.6) in neonates with NT-proBNP levels above 17800 pg/mL.Conclusion Increased NT-proBNP levels may be associated with a significant decrease in BPD-free survival in very immature newborns.
Keywords: neonatal care; brain natriuretic propeptide; bronchopulmonary dysplasia; prematurity